Peran Audit Eksternal dalam Mengidentifikasi dan Menangani Masalah dalam Penyajian Laporan Keuangan: Studi Kasus di Industri Peternakan - Muhammad Nur Maftuh Ihsan; Ratnawati, Dyah (Asosiasi Ahli Administrasi Indonesia, 2025)
This study aims to describe the role of external audit in identifying and resolving problems in the presentation of financial statements in non-public entities, with a case study in the livestock industry. The background of this research is based on the importance of financial statements as a basis for decision making by stakeholders, but in practice, many entities still experience obstacles in preparing financial statements that comply with standards. One of these livestock industries is a company that faces similar challenges, such as manual recording that is not orderly, data discrepancies with current accounts, and a lack of human resources who understand accounting adequately. This research uses a qualitative method with a case study approach, involving direct interviews and documentation studies as data collection techniques. The results show that external audit not only plays a role in providing an opinion on the fairness of financial statements, but also provides strategic recommendations in the form of digitizing records, training human resources, and preparing standard operating procedures. Thus, external audit plays an important role as a strategic partner in improving the quality of financial reporting and overall corporate governance.